2018
DOI: 10.1371/journal.pone.0191451
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of sexual initiation among European adolescents

Abstract: BackgroundSexuality is a physiological component of adolescent development, though early initiation is associated with reproductive health risk. This study aimed at identifying correlates and predictors of sexual initiation in a large multinational cohort of European adolescents.MethodsA questionnaire addressing socio-demographics, behaviours, mental health and sexual activity, was delivered to 11,110 adolescents recruited from 168 randomly selected schools in 10 European countries between 2009 and 2011. A fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 48 publications
2
40
0
8
Order By: Relevance
“…However, the timing of sexual initiation alone may not be considered as an independent marker of risk, as risky sexual activity is often associated with non-sexual risk behaviours (e.g. substance abuse) [ 3 , 9 , 34 , 35 ], exposure to childhood trauma [ 9 , 34 , 36 ] or problematic social interactions (e.g. with peers, school or family) [ 9 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the timing of sexual initiation alone may not be considered as an independent marker of risk, as risky sexual activity is often associated with non-sexual risk behaviours (e.g. substance abuse) [ 3 , 9 , 34 , 35 ], exposure to childhood trauma [ 9 , 34 , 36 ] or problematic social interactions (e.g. with peers, school or family) [ 9 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…smoking or substance abuse), context vulnerabilities (e.g. bullying, truancy and low parental involvement) and psychological difficulties [ 9 ], which are not uncommon among girls and boys [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the onset of sexual activity was not assessed out of concerns that in a multisite trial, the investigators could not assure patient confidentiality relative to their parents/caregivers for all participants. However, obtaining this information in future studies would be helpful in assessing clinical risk and outcomes in patients with chronic diseases (33,34). In children with CKD and on dialysis, contrary to what was believed in the past, recent cohort studies have shown that growth and sexual maturation are only slightly delayed compared to healthy subjects (35).…”
Section: Discussionmentioning
confidence: 99%
“…When we assessed differences in knowledge between genders, women showed more correct answers than men; this is likely because women are the primary focus of HPV vaccination efforts [37,38] and because cervical cancer is strongly correlated with HPV and the first cancer to be associated with HPV infections [39]. Although more women than men knew about the HPV vaccine, women indicated fewer preventive behaviors, reporting less condom use compared to other populations [40]. Knowledge about HPV does not appear to be associated with condom use in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A review of studies performed in college-aged women showed that participants had a lack of information about HPV and the HPV vaccine [59]. Several other studies have reported similar results [33][34][35][36][37][38][39][40][41][42][43][44][45]. In this questionnaire, we decided to not classify the degree of knowledge as sufficient or insufficient because this is a subjective concept.…”
Section: Discussionmentioning
confidence: 99%